Sweet tooth. [5], Unnatural habitats - Lemire, Jeff (DC Comics, 2012)
As the mysterious Captain James Thacker and his crew man a deadly expedition, they will uncover secrets centuries old, but what does any of this have to do with Gus and Jepperd? Plus, while Jeppard, Singh and Gus make plans to head to Alaska, things start to deteriorate for the rest of the group back at the sanctuary!